Book Trailer “Nawung, Puteri Malu dari Jawa” Dengan Teknik Pop-Up Projection Mapping - Nissa Fijriani (Institut Seni Indonesia Yogyakarta, 2020)
Audiovisual medium is an effective medium for conveying information. The arts of videography gives birth to products that can not only displays the expression of it’s creator but also useful. Book trailers have a literacy function that can be a good communication medium for preserving a reading culture by recommending a book. One of audiovisual characteristics which involve more than one human senses to enjoy it has its own power to achieve its purpose. This book trailer takes some parts of the story in the novel “Nawung, Puteri Malu dari Jawa” which arranged into a series of story footage. The compiled plot will be translated into a book trailer format. By using the pop-up projection mapping technique which is a combination of manual techniques (paper cutting and pop-up books) and digital (motion graphics and projection mapping), a book trailer will be made to recommend the novel “Nawung, Puteri Malu dari Jawa”to the wider community.